Endotoxaemia and serum tumour necrosis factor as prognostic markers in severe acute pancreatitis. Issue 8 (August 1992) - Exley, A R; Leese, T; Holliday, M P; Swann, R A; Cohen, J
Abstract : Endotoxaemia and circulating tumour necrosis factor are important prognostic factors in severe sepsis and are implicated in the pathogenesis of septic shock. Because clinical and pathological features in acute pancreatitis are similar to septic shock this study sought to determine whether endotoxin and tumour necrosis factor were prognostic factors in 38 patients with prognostically severe acute pancreatitis. Endotoxaemia, present in 19/37 (51%) patients on day 1, was more common in nonsurvivors than survivors (10/11, 91% v 9/26, 35%, p = 0.003). Day 1 serum endotoxin concentrations were higher in patients with a severe outcome (median (interquartile range) 314 (173-563) pg/ml v 0 (0-185) pg/ml, p<0.01) and in non-survivors (266 (173-586) pg/ml v 0 (0-165) pg/ml, p<0.01). Serum tumour necrosis factor was detectable in 47 of 109 samples (43%) from 38 patients (median 35 pg/ml, range 5-943 pg/ml). Day 1 serum tumour necrosis factor correlated with a worse prognostic score and a severe outcome in all patients (n = 38, r = 0.36, p = 0.027; r = 0.33, p<0.05) and with mortality in patients with gall stones (n = 23, r = 0.50, p = 0.02). Our data suggest that endotoxin and tumour necrosis factor could be prognostic factors in severe acute pancreatitis.